Crystalline inclusion properties of new pyridine and thiophene modified wheel-and-axle diol hosts1. Issue 13 (7th April 2015) - Katzsch, Felix; Weber, Edwin
<x xml:space="preserve">Abstract</x> A new type of pyridine and thiophene group featuring 'wheel-and-axle' hosts showing selective inclusion behavior and potential application as mass sensitive sensor materials in solvent vapor absorption is reported.